Early Psychological Interventions for Somatic Symptom Disorder and Functional Somatic Syndromes: A Systematic Review and Meta-Analysis. Issue 3 (15th April 2022) - Berezowski, Lukas; Ludwig, Lea; Martin, Alexandra; Löwe, Bernd; Shedden-Mora, Meike C.
ABSTRACT: Objective: Psychological treatments for somatic symptom disorder and functional somatic syndromes (SSD/FSS) achieve moderate effects only, potentially because of the high chronicity in these patients. Therefore, we aimed to evaluate whether early treatment, that is, treatment in populations at risk or with recent onset, improves outcome. Methods: We conducted a systematic review and meta-analysis of (cluster-)randomized controlled trials evaluating early psychological interventions in the prevention and treatment of SSD/FSS in adults compared with inactive control conditions, standard care, or placebo. Individuals at risk for SSD/FSS, suffering from subthreshold symptoms or new onsets of SSD/FSS, or presenting with SSD/FSS for the first time were included. Results: We identified 30 eligible studies, mostly examining pain-related conditions. Interventions were diverse, ranging from bibliotherapy to cognitive-behavioral therapy. We found positive effects on depression post-treatment (Hedges' g = 0.12 [95% confidence interval = 0.03–0.2], k = 5) as well as on somatic symptom severity ( g = 0.25 [0.096–0.41], k = 17) and health care utilization ( g = 0.31 [0.18–0.44], k = 3) at follow-up. However, because of a high risk of bias, sensitivity to corrections for meta-bias, and missing outcome data, findings should be interpreted cautiously. Conclusions: Our review shows that targeting SSD/FSS at an early stage represents a conceptual and practical challenge. Readily accessible interventions addressing transsymptomatic processes of SSD/FSS development and consolidation are highly needed. Future studies are needed to evaluate individuals with diverse symptoms, examine symptom history thoroughly, use placebo controls, and report outcomes completely to determine the efficacy of early psychological interventions for SSD/FSS. PROSPERO Registration: CRD42020140122 .